2007
DOI: 10.1186/1744-859x-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry during the Nazi era: ethical lessons for the modern professional

Abstract: For the first time in history, psychiatrists during the Nazi era sought to systematically exterminate their patients. However, little has been published from this dark period analyzing what may be learned for clinical and research psychiatry. At each stage in the murderous process lay a series of unethical and heinous practices, with many psychiatrists demonstrating a profound commitment to the atrocities, playing central, pivotal roles critical to the success of Nazi policy. Several misconceptions led to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
0
33
0
3
Order By: Relevance
“…Instead, he planned a secret action to coincide with his invasion of PolandVfeeling that a war would distract people from the plan. In the fall of 1939, Hitler signed a letter on his personal stationary authorizing Brandt to expand the special treatment killing to adults (Benedict, 2003;Burleigh, 2004;Ost, 2006;Strous, 2007). The letter was issued in October but backdated to September to cover any work that had already been done on the project.…”
Section: Tiergartenstrassementioning
confidence: 97%
See 2 more Smart Citations
“…Instead, he planned a secret action to coincide with his invasion of PolandVfeeling that a war would distract people from the plan. In the fall of 1939, Hitler signed a letter on his personal stationary authorizing Brandt to expand the special treatment killing to adults (Benedict, 2003;Burleigh, 2004;Ost, 2006;Strous, 2007). The letter was issued in October but backdated to September to cover any work that had already been done on the project.…”
Section: Tiergartenstrassementioning
confidence: 97%
“…They used the same carbon monoxide gas for most killings until the development of Zyklon B cyanide gasVwhich killed quicker. One of the T-4 psychiatrists, Irmfried Eberl, became the only physician commandant of a death camp: Treblinka (Strous, 2007).…”
Section: The Holocaust Began With Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Faked death certificates were intended to disguise the deaths as natural in order to hide the victim's fate from their family and the public (Strous 2007). Between 1939 and1941, 80 000 to 100 000 mentally ill people in institutions were killed, including 5000 children (Lifton 2000).…”
Section: Aktion T-4mentioning
confidence: 99%
“…Yet it is not clear that the professionalism of German doctors as a group was less robust than our own. And some have suggested that the incorporation of community values into professional ethics implied by ‘robust professionalism’, when applied in the circumstances of Germany in the 1930s and 1940s, may have contributed to medical collaboration (Strous, ).…”
mentioning
confidence: 99%